2021
DOI: 10.1186/s12917-021-02996-6
|View full text |Cite
|
Sign up to set email alerts
|

Helcococcus ovis associated with septic arthritis and bursitis in calves – a case report

Abstract: Background Septic arthritis often occurs in young calves when the passive transfer of maternal immunoglobulins has failed, which results in hypogammaglobulinaemia in the calf. Another important cause is suboptimal herd health management which often leads to general health impairment and, subsequently, to septic arthritis. Case presentation A dairy farmer consulted the Herd Health Service of the University Clinic reporting general herd health impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The alternative, intrauterine oxytetracycline infusions, remains a frequent practice both in clinical and research settings in the United States and Europe (33,34). Furthermore, dairy operations often use oxytetracycline as prophylactics in heifer rearing or as a treatment for calf pneumonia, a type of infection H. ovis has been implicated in (12). Although the MICs for oxytetracycline were not assessed, there is no inherent difference between a tetracycline and an oxytetracycline resistance genes (35), and 96.8% of isolates in this study carry at least one tetracycline resistance gene shown to confer tetracycline resistance in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative, intrauterine oxytetracycline infusions, remains a frequent practice both in clinical and research settings in the United States and Europe (33,34). Furthermore, dairy operations often use oxytetracycline as prophylactics in heifer rearing or as a treatment for calf pneumonia, a type of infection H. ovis has been implicated in (12). Although the MICs for oxytetracycline were not assessed, there is no inherent difference between a tetracycline and an oxytetracycline resistance genes (35), and 96.8% of isolates in this study carry at least one tetracycline resistance gene shown to confer tetracycline resistance in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Given H. ovis’ recurrent appearance in mixed infections and its apparent reliance on co-occurring bacteria for pyridoxal metabolism, its ability to independently cause extravascular infections is not well established. Co-isolation with other known pathogenic bacteria continued to be a feature of H. ovis isolates from infections in bovine hosts including metritis, mastitis, hepatic abscesses, and septic arthritis [ 4–7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Helcococcus ovis ( H. ovis ) is a Gram-positive, facultative anaerobic, multi-host animal pathogen that often goes undetected due to the specific conditions required for its isolation [ 1 – 3 ]. The bacterium is a recurrent feature in mixed infections in domestic ruminant hosts, including mastitis [ 4 ], pneumonia septic arthritis [ 5 ], and metritis [ 6 ]. Although H. ovis is known to rely on pyridoxal provided by co-occurring bacteria to grow in-vitro, its ability to cause infections independently has been demonstrated [ 4 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium is a recurrent feature in mixed infections in domestic ruminant hosts, including mastitis [ 4 ], pneumonia septic arthritis [ 5 ], and metritis [ 6 ]. Although H. ovis is known to rely on pyridoxal provided by co-occurring bacteria to grow in-vitro, its ability to cause infections independently has been demonstrated [ 4 , 5 , 7 ]. Bovine isolates of H. ovis alone can cause mastitis and synergize with Trueperella pyogenes ( T. pyogenes ) to inflict more severe lesions in the mammary glands of murine infection models [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation